The Impact of AI Use in Learning and Digital Material Accessibility on Students' Academic Achievement through Technology Engagement as A Mediating Variable : The Perspective of Theory of Planned Behaviour and UTAUT Theory - Lestariningrum, Anik; Ausat, Abu Muna Almaududi; Wanof, M. Indre; Pramono, Susatyo Adhi; Syamsuri, Syamsuri (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study aims to analyze the impact of Artificial Intelligence (AI) and digital material accessibility on academic achievement through students' engagement with technology. The research employs a quantitative survey method a survey method using SEM-PLS data analysis to explore the relationships between the relevant variables. A purposive sampling technique is used to select samples that meet specific criteria. The research sample comprises of 162 students in Malang, Indonesia, with data collected via an online questionnaire. This study shows that the use of AI in learning among students in Malang, when combined with effective digital material accessibility, has been proven to have a positive and significant impact on their academic performance, with technology engagement serving as an important mediating variable. AI, by enhancing competence, autonomy, and intrinsic motivation, helps students achieve their academic goals, increases their efforts, and provides higher self-satisfaction. This research implies that effective integration of AI and accessibility of digital materials, supported by technology engagement, can significantly improve students' academic performance, so educational institutions urgently need to strengthen the use of technology in learning.